Rumble in the jungle - Stilton, Geronimo (Geronimo Stilton, 2013)
Traveling to Brazil to locate a rare crystal treasure being guarded by a native tribe in the Amazon jungle, Geronimo Stilton and his friends navigate a treacherous route filled with crocodiles, giant rats and, piranhas.